Применение частотно-резонансного метода обработки данных ДЗЗ в детализационном режиме для оценки нефтегазоносности локального поискового участка - Левашов, С.П.; Батырова, Б.Х.; Якимчук, Н.А.; Корчагин, И.Н.; Божежа, Д.Н. (Геоінформатика, 2017)
Анализируются результаты применения мобильной прямопоисковой технологии для оперативной оценки перспектив нефтегазоносности крупного поискового блока и определения прогнозируемых ресурсов нефти в пределах обнаруженных локальных аномальных зон. Поисковые работы проведены с использованием частотно-резонансного метода обработки и декодирования данных дистанционного зондирования Земли. На этапе рекогносцировочных исследований в пределах Владимирской площади (около 8000 км²), Республика Казахстан, обнаружено и закартировано 27 аномальных зон типа “залежь углеводородов”. Детализационными работами в пределах одной из аномальных зон уточнены ее контуры, установлена центральная точка, в которой проведено вертикальное сканирование разреза, рассчитан объем наиболее перспективных аномально поляризованных пластов типа “нефть”, оценены прогнозируемые ресурсы нефти. Обнаружен вертикальный канал миграции глубинных флюидов. Прямопоисковую технологию рекомендуется использовать в комплексе с традиционными геофизическими методами (прежде всего сейсмическими) для оперативной оценки перспектив нефтегазоносности крупных поисковых блоков и локальных участков. Ее применение может принести значительный эффект при поисках промышленных скоплений углеводородов в нетрадиционных коллекторах. Мобильная технология может также успешно применяться при исследованиях слабоизученных участков и блоков в пределах известных нефте- и газоносных бассейнов. Проаналізовано результати застосування мобільної прямопошукової технології для оперативного оцінювання перспектив нафтогазоносності великого пошукового блока і визначення прогнозованих ресурсів нафти в межах виявлених локальних аномальних зон. Пошукові роботи проведено з використанням частотно-резонансного методу обробки та декодування даних ДЗЗ. На етапі рекогносцирувальних досліджень у межах Володимирської площі, Республіка Казахстан (близько 8000 км²) виявлено та закартовано 27 аномальних зон типу “поклад вуглеводнів”. Деталізаційними роботами в межах однієї з аномальних зон уточнено її контури, встановлено центральну точку, в якій проведено вертикальне сканування розрізу, розраховано об’єм найперспективніших аномально поляризованих пластів типу “нафта”, оцінено прогнозні ресурси нафти. Виявлено вертикальний канал міграції глибинних флюїдів. Прямопошукову технологію рекомендується використовувати в комплексі з традиційними геофізичними методами (насамперед, сейсмічними) для оперативного оцінювання перспектив нафтогазоносності великих пошукових блоків і локальних ділянок. Її застосування може дати значний ефект під час пошуків промислових скупчень вуглеводнів у нетрадиційних колекторах. Мобільну технологію можна успішно застосовувати під час досліджень маловивчених ділянок і блоків у межах відомих нафто- і газоносних басейнів. The purpose of the article is to analyze the application of mobile and direct-prospecting technology for the petroleum potential operative assessment of a large prospecting block and the projected oil resources detected within the discovered local anomalous zones; to improve the methods of prospecting and exploration.
Design/methodology/approach. Mobile technology includes the frequency-resonance method of remote sensing data processing and decoding, and the ground-based geo-electric methods of forming the short-pulsed electromagnetic field (FSPEF) and vertical electric-resonance sounding (VERS). Some methods of technology can be used at various stages of prospecting operations: reconnaissance (assessment of petroleum potential of major search blocks); detailed (assess¬ment of projected oil and gas resources within the individual anomalous zones, detected at the reconnaissance stage of prospecting); the field investigation (ground-based field studies with geo-electric methods FSPEF and VERS to clarify the projected oil and gas resources and to choose the optimal locations of prospecting and exploration wells laying). Findings. At the reconnaissance prospecting research stage within the Vladimirskaya area (approximately 8000 km²), 17 anomalous zones of the “hydrocarbon deposit” type have been detected and mapped. By the detailed works within the “Western” anomalous zone: a) the contours of the anomaly were refined; b) the center point of the anomalous zone was set, in which by the vertical scanning of the cross-section in the range of 700—1700 m the depths and thicknesses of the allocated APL of “oil” and “gas”type were determined; c) based on the data obtained, the volume of the most promising APL of the “oil” type was calculated and the projected oil resources in them were evaluated, which constituted — 35.31 million tons. Within the anomalous zone contours, the vertical channel of deep fluids migration was discovered. On the “Central” anomalous zone at two APL of the “gas” type, the anomalous responses to the resonance frequencies of hydrogen were detected, with one APL — of helium.
Practical significance and conclusions. The direct-prospecting technology may be recommended for use in combination with traditional geophysical methods (seismic, primarily) for an operative assessment of the hydrocarbon potential of major search blocks and local areas. Its application can produce a significant effect during the commercial hydrocarbon accumulations searching in unconventional reservoirs (including the areas of shale spreading, rocks of the Bazhenov formation, coal-bearing formations, and crystalline rocks). Mobile technology can also be successfully used in investigating poorly studied areas and blocks within the known oil and gas-bearing basins.